(untitled) (Research, Society and Development, 2020)
This article discusses the issue of female prison in order to understand the dynamics of the incarceration of women in the metropolitan region of Belém. For this purpose, a search was made in the pertinent literature considering the categorical discussion about female incarceration and a survey of quantitative data, such as secondary, obtained by consulting the Report of the Program “Re-Signifying Lives: care strategy and guarantee of rights”, one of the pillars of the Assistance, Care and Treatment of the “A Hora é Agora” Program carried out within the scope from the Center for Female Re-education in the State of Pará. In the prison are young, single women, with low education, associated with drug trafficking and repeat offenders. The conclusion reached establishes an intrinsic relationship between poverty, unemployment and drug trafficking. The insertion of women with no schooling into society occurs via links to trafficking in the large peripheries in order to guarantee their family’s subsistence.